2017
DOI: 10.1308/rcsann.2016.0356
|View full text |Cite
|
Sign up to set email alerts
|

Patellar reconstruction following previous patellectomy: a review of the literature and a case series using distal femoral autograft during total knee arthroplasty

Abstract: During total knee arthroplasty, the reconstruction of the patella following a previous patellectomy is challenging, and is undertaken to improve functional outcomes and patient satisfaction. In this case series, we have reconstructed the patella using a femoral condyle resected during total knee arthroplasty. The resected femoral condyle with best available bone stock is selected and secured to the extensor mechanism. We reviewed the preoperative indications and postoperative outcomes of two patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Autograft bone can be harvested from the medial femoral condyle or tibial plateau through distal cutting[ 21 , 23 - 25 ]. While both techniques are generally reliable, our case presented challenges due to the size due to the size of the medial femoral condyle, particularly in cases of severe valgus knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autograft bone can be harvested from the medial femoral condyle or tibial plateau through distal cutting[ 21 , 23 - 25 ]. While both techniques are generally reliable, our case presented challenges due to the size due to the size of the medial femoral condyle, particularly in cases of severe valgus knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…We attribute our success to the meticulous placement of the fragmented autograft bone in a press-fit manner within the intra-tendon pocket, facilitating optimal patellar tracking, and securing closure with strong sutures to prevent graft migration. Despite the potentially compromised vascularity of the extensor mechanism due to prior surgeries, our patellar reconstructions have maintained bone integrity on radiographs two years post-operation, showing no signs of resorption[ 21 , 37 ]. Though the long-term viability of the bone graft remains uncertain, our hypothesis asserts that maintaining the occupied space through patella reconstruction, whether by original bone or fibrous tissue replacement, may suffice to preserve the mechanical integrity of the patella and yield satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods can be divided into 2 types: with and without patellar reconstruction. Approaches with patellar reconstruction reconstruct the patella using autologous distal femur 8 or iliac bone graft 9 or allograft 10 while approaches without patellar reconstruction repair the extensor mechanism with tubeplasty 11 . Leopold et al 12 reported that allograft reconstruction of the extensor mechanism after total knee arthroplasty according to the procedure described by Emerson et al 10 showed a mean extension lag of 59° after a mean follow-up of 39 months and resulted in 4 revision surgeries in 7 cases.…”
Section: Discussionmentioning
confidence: 99%